IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL PEMBELAJARAN PENDIDIKAN PANCASILA KELAS X SMK N 1 SOLOK SELATAN - Perda Yuliana; Asril; Reindy Rudagi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Teams Games Tournament (TGT) cooperative learning model in improving the learning outcomes of tenth-grade students in Pancasila Education at SMK Negeri 1 Solok Selatan. The study employed a qualitative descriptive approach. The research subjects were students of Class X Hospitality 2, while the informants included the Vice Principal for Curriculum Affairs and the Pancasila Education teacher. Data were collected through observation, interviews, tests, and documentation, and analyzed using data reduction, data display, and conclusion drawing with technique triangulation. The findings indicate that the implementation of the TGT model was carried out through the stages of class presentation, teams, games, tournament, and team recognition. The implementation of the model enhanced students’ activeness, collaboration, motivation, and participation in the learning process. Students’ average learning scores increased from 75.00 to 79,00 in Test 1 and further improved to 87,00 in Test 2. These findings demonstrate that the TGT cooperative learning model effectively creates an active, collaborative, and student-centered learning environment, thereby improving students’ learning outcomes in Pancasila Education.